Pengaruh Absorben terhadap Kualitas Fisik Minyak - Tri Ariani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This study aims to determine the effect of aloe vera juice (absorbent) on the quality of cooking oil. Both types of oil are used to fry up to five times the frying pan to fry the tempeh weighing 1000 grams at a temperature of 180C. Furthermore, the oil that has been used up to five times the frying recycled again, by clarifying it using aloe vera juice. To determine the quality of oil used parameters of viscosity, specific gravity, refractive index, and free fatty acids. From the results of the research, it is found that the longer the number of fryers resulted in decreased oil quality. This can be seen from the increase in the number of parameters measured ie the viscosity, density, free fatty acid and decrease in the number of refractive index parameters. After the purification using aloe vera juice, the quality of oil is getting better. It is characterized by the decrease of viscosity, density and free fatty acid. Keywords: Absorbent, Edible Oil